2017
DOI: 10.1539/joh.16-0242-oa
|View full text |Cite
|
Sign up to set email alerts
|

Labor factor barriers to seeking medical services among metropolitan workers: a cross-sectional analysis by sex using the J-SHINE study

Abstract: Objectives: There is limited evidence on the relationship between labor factors and the decision to refrain from seeking medical services. This study aimed to examine how labor factors are related to medical service access among male and female workers in Tokyo and surrounding areas. Methods: We used data from 4,385 respondents to the survey in the Japanese Study on Stratification, Health, Income, and Neighborhood (J-SHINE), an ongoing epidemiologic household panel study. Surveys from 2010 to 2011 were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This conceivably explains why those with white-collar occupations scored higher in the literacy scale than those with blue-collar jobs. Pei and colleagues [ 27 ] found that, compared to their white-collar peers, blue-collar workers were less likely to seek medical care when they were ill. According to a Japanese survey, white-collar workers in large corporations in Japan enjoy higher salaries and greater job security due to lifelong employment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This conceivably explains why those with white-collar occupations scored higher in the literacy scale than those with blue-collar jobs. Pei and colleagues [ 27 ] found that, compared to their white-collar peers, blue-collar workers were less likely to seek medical care when they were ill. According to a Japanese survey, white-collar workers in large corporations in Japan enjoy higher salaries and greater job security due to lifelong employment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple logistic regression analysis was selected as a main analysis. According to a formula proposed by Peduzzi et al [ 44 ], we calculated the minimum required sample size for multiple logistic regression analysis while considering that the prevalence of RSMC among Japanese employees has been reported to be about 50% for both genders [ 45 ] and that the maximum number of independent variables (i.e., the number of continuous variables and dummy variables in the fully adjusted model) was 29 for male and 28 for female employees. As a result, the minimum required sample size was 580 for male and 560 for female employees; therefore, our sample size was considered to have sufficient statistical power for the main analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Levesque et al [ 30 ] suggested access as “opportunity” based on the review of previous studies. International surveys often use a question asking “unmet health care needs” [ 35 ], which are also often used in studies on nationals and migrants in Japan [ 22 , 23 , 36 ].…”
Section: Methodsmentioning
confidence: 99%